1, 2, 4-Triphospholyl anions – versatile building blocks for the formation of 1D, 2D and 3D assemblies12. Issue 22 (14th June 2015) - Heindl, Claudia; Peresypkina, Eugenia V.; Virovets, Alexander V.; Komarov, Vladislav Yu.; Scheer, Manfred
<x xml:space="preserve">Abstract</x> The potential of K[P3C2R2] (R = tBu, Mes) as building blocks in metallo-supramolecular chemistry was investigated and self-assembly processes with Cu(i) halides resulted in the formation of a large variety of unprecedented one-, two- and even three-dimensional aggregates.